Microbiology and Management of Pediatric Liver Abscesses: Two Cases Caused by Streptococcus anginosus Group - Michael Cellucci; Erin Simon; Stephen Eppes (Case Reports in Infectious Diseases)
Pyogenic liver abscesses in the pediatric population are rare occurrences in the developed world. We present two cases of previously healthy males presenting with fever and abdominal pain found to have liver abscesses due to organisms in the Streptococcus anginosus group. The microbiology of S. anginosus along with the management and recommended treatment in children with liver abscesses is discussed.